Resolving Coparenting Dissatisfaction In Couples: A Preliminary Task Analysis Study. - Eira Nunes, Cindy; Pascual‐Leone, Antonio; Roten, Yves; Favez, Nicolas; Darwiche, Joëlle (Journal of Marital & Family Therapy, 2021)
This study explored the change that unfolded when parents resolved their coparenting dissatisfaction during an Integrative Brief Systemic Intervention (IBSI) for parent couples. We conducted a task analysis (Greenberg, 2007) to build a model of resolving coparenting dissatisfaction. We compared a postulated model of change (rational model) based on theoretical and clinical assumptions to the observations of the actual change process that couples experienced in an IBSI (empirical analysis). The empirical analysis was conducted on six IBSI therapy cases (three exhibiting positive development and three exhibiting no development). We defined positive development in IBSI as moving from coparenting dissatisfaction to coparenting satisfaction. The final rational–empirical model included six steps that facilitated the resolution of coparenting dissatisfaction. This study contributes to deepening the knowledge of how coparenting may change during marital therapy.